Hubungan antara Tinggi Badan dan Kekuatan Otot Tungkai dengan Kecepatan Renang Gaya Bebas 25 Meter pada Siswa Kelas VIII SMP Daar El Salam - Fajri, Muflikhul; Mustaqim, Enjang Ahmad (Lentera: Jurnal Ilmiah Kependidikan, 2020)
This study aims to determine (1) whether there is a relationship between the muscle strength of the 25 meter swimming speed at the fifth grade students of Daar El Salam Junior High School. (2) Is there a relationship between height and 25 meter freestyle swimming speed at Daar El Salam Junior High School. (3) Is there a relationship between height and leg muscle tightness with the speed of 25 meter freestyle swimming at Daar El Salam Junior High School. The results of this study indicate that the height there is a correlation coefficient of 0.825 with a very strong relationship level, the strength of the river muscle there is a correlation coefficient of 0.847 with a very strong relationship level, and. Based on the results of linear tests and the significance of a simple regression equation between height, leg muscle strength, and 0.939 with a coefficient of determination (R2) of 0.882, the effect is 88.2% while 11.8% is influenced by other factors not in the variable this research. And the significance test for multiple correlation is 52.32 where the F value is greater than the F table.